Historical Tourism Opportunities In Muzrabad, Surkhandarya Region - Eshbayev Namaz Chori Ogli (Zien Journals, 2021)
Geography of Muzrabad district, historical tourism opportunities in muzrabad district, surkhandarya region, tourism opportunities of historical monuments of Muzrabad district were considered.
Keywords: district geography; tourism; tourism geography; historical tourism,